Patterns and influence of familial autoimmunity in pediatric systemic lupus erythematosus - Walters Heather M; Pan Nancy; Moorthy Lakshmi N; Ward Mary J; Peterson Margaret G; Lehman Thomas J (BMC, 2012)
Abstract Background A high prevalence of autoimmune disease (AD) has been documented in relatives of adult patients with systemic lupus erythematosus (SLE). However, data on familial inheritance patterns in pediatric SLE patients is scarce. Findings The charts of 69 patients with pediatric-onset SLE were reviewed retrospectively. The primary aim was to describe the prevalence and types of AD in relatives of children with SLE. The secondary aims were: 1) to compare severity of SLE in children with and without relatives affected by AD, and 2) to evaluate the impact of baseline demographics on severity of SLE in subjects. At diagnosis, 42% of subjects had one or more first, second, or third degree relative(s) with AD; and 32% of subjects had one or more first degree relative(s) with AD. The most common diseases in relatives of children with SLE were SLE (21%) and thyroid disease (15%). Subjects with no family history of AD were more likely to have severe SLE. SLE severity in subjects did not differ by gender. Children presenting with SLE at an earlier age were found to have more severe disease. Conclusions This study demonstrated a high prevalence of AD in families of children with SLE, although a family history of AD did not correlate with more severe SLE in subjects. Future larger studies are necessary to elucidate patterns of familial inheritance and baseline patient characteristics that may affect severity of disease in pediatric SLE.